Pengaruh Kepemimpinan Dan Budaya Organisasi Terhadap Kepuasaan Kerja Pegawai Pada Kantor Camat Ambalawi Kabupaten Bima - Miratunnisah Miratunnisah; Mauhammad Yusuf (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
The purpose of this research is to determine the influence of Leadership and Organizational Culture on Employee Job Satisfaction at the Ambalawi Subdistrict Office, Bima Regency. This type of research is associative research, where the population is 40 people with a sample of 39 employees who work at the Ambalawi Subdistrict Office, Bima Regency. Samples were taken using purposive sampling technique. The data analysis methods used are reliability and validity tests, classical assumption tests, T tests and F tests, correlation coefficients, determination tests and multiple linear regression analysis. Based on the results of data analysis using the t test, it shows that there is a positive and significant influence of leadership (X1) on job satisfaction (Y) at the Ambalawi sub-district office, Bima district. There is a positive and significant influence of organizational culture on job satisfaction at the Ambalawi sub-district office, Bima district. Based on the F test calculation, leadership (X1) and organizational culture (X2) simultaneously influence job satisfaction (Y) at the Ambalawi sub-district office, Bima district.